Meningkatkan Kemampuan Berpikir Kreatif Matematis dan Kemampuan Pemecahan Masalah Siswa SMP melalui Model Pembelajaran Koeperatif Tipe STAD Berbantuan Slide Master - Asmudi Asmudi (Jurnal Peluang, 2019)
This study aimed to examine the differences in the increase in the ability to think kreatif mathematical and mathematical problem solving significant difference between students who obtain mathematical learning model STAD learning model koeperatif assisted Slide Master and students who obtain teaching with conventional approaches. This study was an experimental group and a control group. The experimental group gained learning by using learning model STAD koeperatif and gain control group of conventional learning. To get the research data used instrument in the form of creative thinking ability tests of mathematical and mathematical problem solving. This research was conducted in SMP Negeri 1 Kuala Bireuen. The study population was all students in grade VIII SMP Negeri 1 Kuala Bireuen with sample is a class VIII student of two classes were selected purposively from the existing nine classes. The data were analyzed quantitatively. Quantitative analysis is performed against the average gain is normalized between the two sample groups using t-test. The results showed that the study of mathematics by using learning model STAD koeperatif aided Slide Master can upgrade mathematical creative thinking and problem solving mathematical kemempuan students overall. Learning mathemathics using models koeperatif STAD Slide Master aided significantly better in improving the mathematical ability of creative thinking and mathematical problem solving ability of students compared to conventional learning. Learning to use the model STAD koeperatif can be an alternative model of learning approaches that can be used in Junior High.